The elusive early medieval glass : remarks on vessels from the Nin - Ždrijac cemetery, Croatia = Izmikajoče se zgodnjesrednjeveško steklo : komentar k posodam z grobišča Nin - Ždrijac, Hrvaška - Milavec, Tina (Array, 2018)
In graves 322 and 310 of the early medieval Nin – Ždrijac cemetery three glass vessels, two stemmed goblets and one bottle were found. They have been interpreted as remains of Late Antique glass production, but a closer look brings further information. The best comparisons for the goblets come from the North Adriatic area while the bottle is most probably of early Islamic production. Interesting possibilities of interpretation arise with the graves being furnished with glass products of such different origin at a time when local secondary glass production seems to have been absent.